2023
DOI: 10.3389/fnut.2023.1166702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different n-6/n-3 polyunsaturated fatty acids ratios on lipid metabolism in patients with hyperlipidemia: a randomized controlled clinical trial

Abstract: Background and aimsIntake of n-3 polyunsaturated fatty acids (PUFA) is helpful for cardiometabolic health. It improves lipid metabolism, and increasing n-3 PUFA is often considered beneficial. However, the role of n-6/n-3 in the regulation of lipid metabolism has been much debated. Therefore, this study was performed on the effect of different proportions of n-6/n-3 diet on lipid metabolism, and quality of life in patients with hyperlipidemia, aiming to explore appropriate proportions of n-6/n-3 to provide the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…It is hypothesized that all PUFAs in the diet can depress low-density lipoprotein cholesterol (LDL-C) and lower serum cholesterol levels, whereas all SFAs contribute to high levels of the latter. The results of a recent clinical study confirm the positive influence of PUFAs on high-density lipoprotein cholesterol (HDL-C) levels and total cholesterol—the levels of the former were increased, while those of the latter decreased [ 20 ].…”
Section: Resultsmentioning
confidence: 90%
“…It is hypothesized that all PUFAs in the diet can depress low-density lipoprotein cholesterol (LDL-C) and lower serum cholesterol levels, whereas all SFAs contribute to high levels of the latter. The results of a recent clinical study confirm the positive influence of PUFAs on high-density lipoprotein cholesterol (HDL-C) levels and total cholesterol—the levels of the former were increased, while those of the latter decreased [ 20 ].…”
Section: Resultsmentioning
confidence: 90%
“…Another challenge is the scarcity of human studies on supplementation with n-3 PUFA in melanoma and other cancers. Over the past decades, there has been a shift in dietary patterns in the current human population compared to our ancestors, and modulating the n-6/n-3 ratio has been considered an intriguing point in the research field across various pathologies [181][182][183][184]. However, a randomized controlled trial showed that supplementation with n-3 PUFA did not result in a lower incidence of major cardiovascular events or cancer than placebo [185].…”
Section: Discrepancy In Results and Approaches To Studies In Humansmentioning
confidence: 99%
“…(Van Name et al, 2020) The ratio of n-6/n-3 PUFA is known to play a signi cant role in lipid metabolism regulation. (Yang et al, 2023) Recent clinical studies have demonstrated that reducing the n-6/n-3 PUFA ratio can lead to lower lipid levels and weight loss. These ndings may help explain the inverse correlation observed between EPA and AA in mouse phenotypes.…”
Section: Discussionmentioning
confidence: 99%